Answer:
Option A - ![-\frac{5}{6}(x-\frac{1}{2}y+12)=-\frac{5}{6}x+\frac{5}{12}y-10](https://tex.z-dn.net/?f=-%5Cfrac%7B5%7D%7B6%7D%28x-%5Cfrac%7B1%7D%7B2%7Dy%2B12%29%3D-%5Cfrac%7B5%7D%7B6%7Dx%2B%5Cfrac%7B5%7D%7B12%7Dy-10)
Step-by-step explanation:
Given : Expression ![-\frac{5}{6}(x-\frac{1}{2}y+12)](https://tex.z-dn.net/?f=-%5Cfrac%7B5%7D%7B6%7D%28x-%5Cfrac%7B1%7D%7B2%7Dy%2B12%29)
To find : Which expression is equivalent to given expression ?
Solution :
Expression ![-\frac{5}{6}(x-\frac{1}{2}y+12)](https://tex.z-dn.net/?f=-%5Cfrac%7B5%7D%7B6%7D%28x-%5Cfrac%7B1%7D%7B2%7Dy%2B12%29)
Applying distributive property, ![a(b+c)=ab+ac](https://tex.z-dn.net/?f=a%28b%2Bc%29%3Dab%2Bac)
![-\frac{5}{6}(x-\frac{1}{2}y+12)=-\frac{5}{6}x-(-\frac{5}{6})(\frac{1}{2}y)+(-\frac{5}{6})(12)](https://tex.z-dn.net/?f=-%5Cfrac%7B5%7D%7B6%7D%28x-%5Cfrac%7B1%7D%7B2%7Dy%2B12%29%3D-%5Cfrac%7B5%7D%7B6%7Dx-%28-%5Cfrac%7B5%7D%7B6%7D%29%28%5Cfrac%7B1%7D%7B2%7Dy%29%2B%28-%5Cfrac%7B5%7D%7B6%7D%29%2812%29)
![-\frac{5}{6}(x-\frac{1}{2}y+12)=-\frac{5}{6}x+\frac{5}{12}y-10](https://tex.z-dn.net/?f=-%5Cfrac%7B5%7D%7B6%7D%28x-%5Cfrac%7B1%7D%7B2%7Dy%2B12%29%3D-%5Cfrac%7B5%7D%7B6%7Dx%2B%5Cfrac%7B5%7D%7B12%7Dy-10)
Therefore, option A is correct.
Answer:
The value for 6 is ones that's the answer
Answer:help pls
Step-by-step explanation: